2009
DOI: 10.1186/1749-8104-4-7
|View full text |Cite
|
Sign up to set email alerts
|

Wnt activity guides facial branchiomotor neuron migration, and involves the PCP pathway and JNK and ROCK kinases

Abstract: Background: Wnt proteins play roles in many biological processes, including axon guidance and cell migration. In the mammalian hindbrain, facial branchiomotor (FBM) neurons undergo a striking rostral to caudal migration, yet little is known of the underlying molecular mechanisms. In this study, we investigated a possible role of Wnts and the planar cell polarity (PCP) pathway in this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
125
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(135 citation statements)
references
References 66 publications
(95 reference statements)
10
125
0
Order By: Relevance
“…We favor a model in which the importance of the second cell is not in having pioneer-like capacity, but rather in being the closest FBMN to the pioneer, serving to link the pioneer to follower FBMNs. Much previous work examining FBMN migration has focused on the PCP pathway; several labs have shown that multiple components of the PCP pathway are crucial for FBMN migration both in zebrafish and in mouse Jessen et al, 2002;Carreira-Barbosa et al, 2003;Bingham et al, 2005;Wada et al, 2005;Wada et al, 2006;Rohrschneider et al, 2007;Vivancos et al, 2009;Qu et al, 2010;Walsh et al, 2011;Glasco et al, 2012). Our analysis of pioneer neurons and the MLF supports a model in which FBMN migration requires additional inputs beyond PCP signaling.…”
Section: Research Articlesupporting
confidence: 67%
“…We favor a model in which the importance of the second cell is not in having pioneer-like capacity, but rather in being the closest FBMN to the pioneer, serving to link the pioneer to follower FBMNs. Much previous work examining FBMN migration has focused on the PCP pathway; several labs have shown that multiple components of the PCP pathway are crucial for FBMN migration both in zebrafish and in mouse Jessen et al, 2002;Carreira-Barbosa et al, 2003;Bingham et al, 2005;Wada et al, 2005;Wada et al, 2006;Rohrschneider et al, 2007;Vivancos et al, 2009;Qu et al, 2010;Walsh et al, 2011;Glasco et al, 2012). Our analysis of pioneer neurons and the MLF supports a model in which FBMN migration requires additional inputs beyond PCP signaling.…”
Section: Research Articlesupporting
confidence: 67%
“…In the nervous system, Fz receptors mediate a range of functions from neuronal differentiation (Van Raay et al, 2005) to cell survival Wang et al, 2001), cell polarity (Prasad and Clark, 2006), cell migration (Pan et al, 2006;Vivancos et al, 2009), axon guidance (Lyuksyutova et al, 2003;Wang et al, 2002) and synapse formation (Varela-Nallar et al, 2009;Klassen and Shen, 2007). Here, we focus our attention on Fz5, previously shown to regulate neuronal development .…”
Section: Discussionmentioning
confidence: 99%
“…In the nervous system, Fzs mediate a range of functions from neuronal differentiation (Van Raay et al, 2005) to cell polarity (Prasad and Clark, 2006), cell migration (Pan et al, 2006;Vivancos et al, 2009), axon guidance (Lyuksyutova et al, 2003;Wang et al, 2002) and cell survival . In Drosophila, the Wnt protein Wingless (Wg) activates the Fz2 receptor, present at both sides of the neuromuscular synapse, to regulate pre-and postsynaptic signalling (Ataman et al, 2008;Packard et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This finding stems primarily from studies of mouse and zebrafish facial branchiomotor neurons (FBMNs), which originate ventrally in hindbrain rhombomere (r)4 and undergo highly stereotypical posterior migration along the floorplate to r6 and r7 (Wanner et al, 2013). Mutations in the genes encoding Vangl2, Pk1, Fz3 and Celsr2 all prevent FBMN migration in zebrafish and mice, as do Scrib and Ptk7 mutations Glasco et al, 2012;Mapp et al, 2011;Qu et al, 2010;Vivancos et al, 2009;Wada et al, 2005Wada et al, , 2006Yang et al, 2014) (Table 1). The role of Wnt ligands in FBMN migration is uncertain: mice lacking Wnt5a have a mild defect whereas Wnt4a, Wnt5a and Wnt11r mutants in zebrafish all exhibit normal FBMN migration (Vivancos et al, 2009) (our unpublished results).…”
Section: Pcp Signaling In Neuronal Migrationmentioning
confidence: 99%